The Increased Impact of Mass Mediated Visual Imagery on Christian Oratory - Schnell, Jim (International Journal of Mass Communication, 2023)
This report conveys speculations having to do with the increased emphasis on visual imagery over aural messages and the subsequent impact on Christian oratory as it relates to evangelism. As we move to being a more visually oriented society, via web based and new communication technologies, aural forms of communication that generally have more emphasis on critical thinking are being displaced by the visual domain that stresses more imaginary associations. A central finding is that the visual dominates at the expense of the aural and the imagination presides over critical thinking.